Selective CO2 adsorption and bathochromic shift in a phosphocholine-based lipid and conjugated polymer assembly. Issue 14 (16th March 2022) - Noh, Juran; Koo, Dong Geon; Hyun, Chohee; Lee, Dabin; Jang, Seohyeon; Kim, Jiho; Jeon, Yejee; Moon, Su-Young; Chae, Boknam; Nam, Inho; Shin, Tae Joo; Park, Juhyun
Abstract : Assembly films of a phosphocholine-based lipid and a crystalline conjugated polymer had significant CO2 selective adsorption and light absorption due to the attractive interaction of CO2 with exposed polar lipid heads and enhanced morphologies. Abstract : We assemble a film of a phosphocholine-based lipid and a crystalline conjugated polymer using hydrophobic interactions between the alkyl tails of the lipid and alkyl side chains of the polymer, and demonstrated its selective gas adsorption properties and the polymer's improved light absorption properties. We show that a strong attractive interaction between the polar lipid heads and CO2 was responsible for 6 times more CO2 being adsorbed onto the assembly than N2, and that with repeated CO2 adsorption and vacuuming procedures, the assembly structures of the lipid-polymer assembly were irreversibly changed, as demonstrated by in situ grazing-incidence X-ray diffraction during the gas adsorption and desorption. Despite the disruption of the lipid structure caused by adsorbed polar gas molecules on polar head groups, gas adsorption could promote orderly alkyl chain packing by inducing compressive strain, resulting in enhanced electron delocalization of conjugated backbones and bathochromic light absorption. The findings suggest that merging the structures of the crystalline functional polymer and lipid bilayer is a viable option for solar energy-converting systems that use conjugated polymers as a light harvester and the polar heads as CO2 -capturing sites.